A dictionary of modern English usage - Fowler, H. W. (Henry Watson), 1858-1933.; Crystal, David, 1941- (Oxford ; New York : Oxford University Press, 2009)
"No book had more influence on twentieth century attitudes to the English language in Britain than Henry Fowler's Dictionary of Modern English Usage. It rapidly became the standard work of reference for the correct use of English in terms of choice of words, grammar, and style. Much loved for his firm opinions, passion, and dry humour, Fowler has stood the test of time and is still considered the best arbiter of good practice. One of today's leading experts on the language, David Crystal, has now reassessed Fowler's contribution in this new edition." "Crystal goes beyond the popular mythology surrounding Fowler's reputation to retrace his method and practice and arrive at a fresh evaluation of his place in the history of linguistic thought. With a wealth of entertaining examples he looks at Fowler's stated principles and the tensions between his prescriptive and descriptive temperaments. He reaches some surprising conclusions and shows that the Dictionary does a great deal more than make normative recommendations and express private opinions. In addition he offers a modern perspective in notes on some 300 entries, in which he shows how English has changed since the 1920s."--BOOK JACKET.
Originally published: Oxford : The Clarendon Press, 1926. With new introd.
Includes bibliographical references.
Keywords: English language -- Usage -- Dictionaries